Pendugaan Cadangan Karbon Tersimpan Pada Kelapa Sawit (Elaeis guineensis Jacq.) Dan Analisis Kesuburan Tanah di Perkebunan PT Daria Dharma Pratama Ipuh Bengkulu - Yuliyanto . (JURNAL CITRA WIDYA EDUKASI, 2018)
The increasing concentration of carbon in the atmosphere is a serious environmental problem that can affect living systems on earth. The increase in greenhouse gas (GHG) emissions caused global warming. The impact of global warming will affect the world climate change and rising sea levels. Climate change will disrupt farming systems in both the micro and macro scale. Estimation of forest carbon emissions is one of the important efforts to reduce climate change. Land clearing for oil palm plantations will affect the carbon stored in the forest reserves. This study aims to determine the carbon stocks stored in oil palm in each age group on the type of red-yellow podzolic soil in Oil Palm Plantation PT Daria Dharma Pratama Bengkulu. Method of measuring the carbon content of oil palm biomass using non-destructive method with allometric equations. Measurement of biomass carbon content stored conducted in every age group of plants. The result showed the content of carbon stored in plants palm largest (carbon biomass) on red-yellow podzolic soil in PT DDP Oil Palm Plantations are in the age group 11-15 years was 65.89 ton/ha. Then a row in the age group 16-20 years was 51.74 ton/ha, the age group> 20 years of 33.07 ton/ha, the age group 6-10 years at 31.86 ton/ha, and the age group 0-5 years of 1.61 ton/ha. Carbon content stored on palm influenced by plant age, and the growth and development of plants. Group relationship with the age of the plant oil palm biomass carbon content tend to show a sigmoid pattern. Growth and development of oil palm plantations is affected by the physical properties and chemical soil.